VP54 Costs And Benefits Of Intensive Inpatient Rehabilitation After Stroke. (2017) - Suh, Youshin; Ahn, Jeonghoon
Abstract : INTRODUCTION: This study estimated, from the societal perspective, the costs and benefits of the intensive inpatient rehabilitation treatments (IIRT) on patients after stroke using the interim results of a large ongoing registry in Korea, the Korean Stroke Cohort for Functioning and Rehabilitation (KOSCO) (1). METHODS: Among others, the benefits were measured by two major cost savings: (i) decrease in government disability subsidy and (ii) caregiver savings. One of the KOSCO study results showed the functional status of the post-stroke patients, measured by the Korean Modified Barthel Index (K-MBI), improved significantly and the disability grades, which the government is using to classify the subsidy amount, reduced as well. Caregiver cost savings were calculated by K-MBI improvements, the average daily compensation of caregivers (USD58.33) and the average period of caregiving. To measure the cost of IIRT on post-stroke patients, the average costs reported by a National Evidence-based Healthcare Collaboration Agency (NECA) Health Technology Assessment report was used (2). RESULTS: The disability grade improvements showed savings of government subsidy by USD58.65 to USD478.39 depending on the patient income from the registry. The average caregiving cost decrease was USD6, 042 annually. The average cost of IIRT on post-stroke patients was USD926.34 for the first year. CONCLUSIONS: This study estimated the cost-benefit of IIRT on post-stroke patients using the KOSCO study interim data. The intensive rehabilitation treatment improves patients functional status significantly enough to save two major cost items, the disability grades which also resulted in a decrease in government subsidy amounts and the caregiver costs which the patient family has to pay in Korea. The results warrant the use of IIRT for the post-stroke patients in Korea from the societal perspective.